Silibinin pretreatment attenuates biochemical and behavioral changes induced by intrastriatal MPP+ injection in rats - Geed M.; Garabadu D.; Ahmad A.; Krishnamurthy S. (My University, 2025)
Silymarin commonly known for its hepatoprotective effect is reported to show protection against 6-hydroxydopamine-induced neurotoxicity. Silibinin forms the major active constituent of silymarin. Therefore, the neuroprotective effect of silibinin (50, 100 and 200 mg/kg) was evaluated in the unilaterally injected 1-methyl-4-phenylpyridinium (MPP+)-induced dopaminergic neurotoxicity in male rats. A battery of tests such as elevated plus maze (EPM), narrow beam walk, open field, bar catalepsy, grip strength, and foot print analysis was performed to evaluate the behavioral symptoms of striatal dopaminergic toxicity. Furthermore, the mechanism of action of silibinin was investigated by evaluating the mitochondrial complex enzyme activities, mitochondrial integrity and oxidative status. Striatal caspase-3 and NFκB were expressed to evaluate the effect of silibinin on apoptosis and inflammation respectively. Silibinin (100 and 200 mg/kg) protected against MPP +-induced dopamine depletion in striatum. Silibinin reversed MPP +-induced decrease in transfer latency indicating memory consolidation in the EPM test. Silibinin (100 and 200 mg/kg) attenuated MPP +-induced motor deficits, such as fine motor movements and gait. MPP+-induced mitochondrial dysfunction, loss of integrity and oxidative stress were attenuated by silibinin. Silibinin decreased striatal caspase-3 and NFκB expression indicating potential anti-apoptotic and anti-inflammatory effects respectively. Hence, silibinin exhibited neuroprotective effect in the MPP+ induced striatal toxicity augmenting dopamine levels. The mechanism of action may be linked to maintenance of mitochondrial bioenergetics and integrity apart from anti-apoptotic and anti-inflammatory activities. © 2013 Elsevier Inc.